Physico-chemical properties of ‘wara’ cheese precipitated with sodom apple and pawpaw leaf juice (2010)
A study was conducted to access the physicochemical properties of ‘wara’ cheese precipitated with sodom apple or pawpaw leaf juice. These coagulants ware applied to fresh Zebu milk or reconstituted milk powder at 50' C arid heated slowly until boiling point was reached. Chemical composition of both milk showed that fresh Zebu milk had higher fat, lactose and total solids than reconstituted milk powder. Crude protein content of cheese coagulated with Sodom apple was lower than those coagulated wiih pawpaw leaf Juice. However, cheese precipitated with sodom apple required a highs- volume (10ml) of juice per- litre of milk than rrieeie precipitated cheese pawpaw leaf /8ml) juice. Organoleptic assessment also revealed that cheese precipitated with sodom apple were preferred to cheese precipitated with pawpaw leaf extract. The higher protein content and preference of consumers for sodom apple-precipitated cheese, probably explain why this coagulant is prefared among local cheese makers